(3JMbjb GdeSDhdjI aj GdJYdje GdYGdjs (3GdJhGRf Hjf GdeWGdH GdYGeI, h GdCcGOjejI h GdNGUI HGdShbs - (3HjQc, LhRja Sjs; (3ESHQ, CSGeI eMeOs; (3YThj, eUWais ((3GdQjGVs (3ecJHI GdYHjcGfs, 2006)
(3jLeY gPG GdcJGH GdBQGA GdYejbI dKdI ef CQhY GdHGMKjf aj GdHdGO Mhd ehVhY GdeSDhdjI Gdege LOG aj GdJYdje GdYGdi h ef GdeQLM Gf jUHM eQLYG TGedG h LGeYG dYfGUQ GdehVhY aj GdSfhGJ GdbGOeI hjVjA gPG GdcJGH GdPci GdJhJQ GdOGNdi Hjf GdeSDhdjI h GdGSJbdGdjIs
(3GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdEfLdjRjIs
1 13 18
Keywords: (3GdJYdje GdLGeYjs; (3GdLGeYGJ h GdcdjGJs -- (3JfXje h EOGQIs